PROSEDUR DAN METODE PENERJEMAHAN LIRIK LAGU DALAM FILM FROZEN - Jong, Hwayeon; Oeinada, I Gede; Luhur Wedayanti, Ni Putu (Humanis, 2017)
The title of this research is “The Translation Procedure and Method of song lyrics from film Frozen” This research described the translation procedure and method which applied on film Frozen’s song lyrics. The theories used in this research were translation procedure by Vinay and Darbelet (2000) and translation method by Newmark (1998). The data resources are 3 songs of film Frozen which is Let It Go, Do You Want To Build A Snowman? and For The First Time In Forever. The data were analyzed with equal method and technique of selective decisive element. The results of this research show that from 105 translation datas, 2 datas are translated with borrowing procedure, 1data is translated with literal translation procedure, 12 datas are translated with transpositions procedure, 67 datas are translated with modulation procedure and 12 datas are translated with equivalence procedure. Also orientation of the translation method is the target languages.
Keywords: song lyrics translation, translation procedure, translation method